PRODUCTIVITY OF KORIANDUR DEPENDING ON TERMS OF SAWING, NORMS OF EXTENSION AND SHIRINES IN THE NORTHERN STEP OF UKRAINE - Козелець, Г. М. (Scientific Progress & Innovations, 2013)
The results of investigations of the effect of seed rate and row spacing on the productivity of coriander on the podzim and early spring yields are given. It was established that the best seeding period for coriander is the podzimovy, in which the fruit yield was 1.21 t / ha, which is more compared to the early spring by 0.30 t / ha, or 24.7%. For a coriander in the conditions of the northern steppe, the seeding rate of 2.0-2.5 million cu is optimal. us. per 1 hectare, which yields 1.14-1.15 t / ha. A seam with a width of 0.45 m row spacings contributed to yielding 1.09 t / ha, which is more than 0.15 m at 0.06 t / ha, or 8.0%. The highest level of harvest (1.39 t / ha) was obtained for the podium seeding period with a width of rows of 0.45 m and a seeding rate of 2.0 million growing seeds per 1 hectare.